Organic Nitrate Maintains Bone Marrow Blood Perfusion in Ovariectomized Female Rats: A Dynamic, Contrast-Enhanced Magnetic Resonance Imaging (MRI) Study - Yu Huang; Tao Gu; Hing Lok Wong; Min Deng; Chun Hay Ko; James F. Griffith; Yi-Xiang J. Wang (MDPI AG, 2012)
This study investigated the effects of nitrate on bone mineral density (BMD) and bone marrow perfusion in ovariectomized (OVX) female rats, and also the effects of nitrate on in vitro osteoblastic activity and osteoclastic differentiation of murine monocyte/ macrophage RAW 264.7 cells. Female Sprague-Dawley rats were divided into OVX + nitrate group (isosorbide-5-mononitrate, ISM, 150 mg/kg/ day b.i.d), OVX + vehicle group, and control group. Lumbar spine CT bone densitometry and perfusion MRI were performed on the rats at baseline and week 8 post-OVX. The OVX rats' BMD decreased by 22.5% ± 5.7% at week 8 (p < 0.001); while the OVX + ISM rats' BMD decreased by 13.1% ± 2.7% (p < 0.001). The BMD loss difference between the two groups of rats was significant (p = 0.018). The OVX rats' lumbar vertebral perfusion MRI maximum enhancement (Emax) decreased by 10.3% ± 5.0% at week 8 (p < 0.005), while in OVX + ISM rats, the Emax increased by 5.5% ± 6.9% (p > 0.05). The proliferation of osteoblast-like UMR-106 cells increased significantly with ISM treatment at 0.78 µM to 50 μM. Treatment of UMR-106 cells with ISM also stimulated the BrdU uptake. After the RAW 264.7 cells were co-treated with osteoclastogenesis inducer RANKL and 6.25 μM ~ 100 μM of ISM for 3 days, a trend of dose-dependent increase of osteoclast number was noted.